2015
DOI: 10.1016/j.celrep.2014.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Ezh2 Depletion in Glioblastoma Causes a Robust Switch in Cell Fate Resulting in Tumor Progression

Abstract: EZH2 is frequently overexpressed in glioblastoma (GBM), suggesting an oncogenic function that could be a target for therapeutic intervention. However, reduced EZH2 activity can also promote tumorigenesis, leading to concerns about the use of EZH2 inhibitors. Here, we provide further insight about the effects of prolonged Ezh2 inhibition in glioblastoma using preclinical mouse models and primary tumor-derived human GBM cell lines. Using doxycycline-inducible shRNAs that mimic the effects of a selective EZH2 inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 50 publications
2
55
1
Order By: Relevance
“…While the former is expected to control the immediate biological response to Ezh2 inhibition, the latter, by increasing the plasticity of gene expression programs, might lead to long-term responses. Such a distinction between early and late response to Ezh2 inhibition was recently reported in a model of glioblastoma in which prolonged knockdown of Ezh2 results in the emergence of "escaper" tumors characterized by an aggressive phenotype (de Vries et al 2015). It is tempting to speculate that the transcriptional instability of Polycomb targets as a consequence of Ezh2 knockdown might have fueled the emergence of escaper tumors.…”
Section: Discussionmentioning
confidence: 98%
“…While the former is expected to control the immediate biological response to Ezh2 inhibition, the latter, by increasing the plasticity of gene expression programs, might lead to long-term responses. Such a distinction between early and late response to Ezh2 inhibition was recently reported in a model of glioblastoma in which prolonged knockdown of Ezh2 results in the emergence of "escaper" tumors characterized by an aggressive phenotype (de Vries et al 2015). It is tempting to speculate that the transcriptional instability of Polycomb targets as a consequence of Ezh2 knockdown might have fueled the emergence of escaper tumors.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, prolonged inhibition of PcG proteins might cause adverse effects, as we have recently shown that continued EZH2 depletion in a mouse model for glioblastoma multiforme caused accelerated tumor growth after an initial growth-reduction response. 155 Overactivation or complete inactivation might be oncogenic, while a window of opportunity lies between activation levels utilized in the homeostasis of normal tissue. Evidently, this window varies from tissue to tissue and depends on the tumor-driving mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, reestablishing H3K27 methylation or PRC2 complex functionality might represent therapeutic approaches for pediatric HGGs with mutations at K27. However, care must be taken when considering this approach, because H3K27 hypermethylation can drive initiation of other brain tumors, and the role of the PRC2 complex is context-dependent, with increased activity leading to more aggressive stages in other malignancies (198)(199)(200)(201). A recently published chemical screen in patient-derived DIPG cultures identified a histone-modifying combination therapy comprising the multi-HDAC inhibitor panobinostat and the histone demethylase inhibitor GSK-J4 as being effective both in vitro and in DIPG orthotopic xenograft models (202), making this an interesting strategy for further validation.…”
Section: K27 and G34 Tumor Subgroupsmentioning
confidence: 99%